Optimizing Production by Increasing the Speed of Komatsu HD 785-7 PT Kalimantan Prima Persada Site Indexim Kaliorang, East Kutai, East Kalimantan - Deni Riski Ramadan; Yoszi Mingsi Anaperta (Journals Mining Engineering : Bina Tambang, 2024)
PT. Kalimantan Prima Persada Jobsite Indexim is mining company operating in the field of coal mining contractors. From the results of observations, the influence on the non-achievement of Productivity is the condition of the haul road is not in accordance with the standards and the performance of hauler operators is not optimal. Therefore, to achieve the overburden and coal production targets that have been set, it is necessary to pay attention to several things, namely tool work efficiency, tool cycle time, and haul road conditions. The stages used to determine the ideal standard for mining roads use 3 reference parameters, the first is based on the AASHTO (American Association of State Highway and Transportation Officials) method, Ministerial Decree of the Ministry of Energy and Mineral Resources (ESDM) in 2018, and the KPP Road Management System. In this research, the type of research used is quantitative research. The results and discussion show that the increase in the average speed of the HD785-7 from April to July which has an effect on increasing the productivity of the HD 785 with the best achievement at 232 BCM/hour.